Content and face validity in virtual reality with children: a validation in five steps+1 of a wheelchair basketball game - Ceberio, Imanol; Al-Rashaida, Mohammad; García, Maitane; Lopez Paz, Juan Francisco; Salgueiro, Monika; Passi, Nicole; Pavel, Humberto; Amayra, Imanol (Frontiers in Virtual Reality, 2025)
Objective: The present study is aimed to elaborate and determinate the content and face validity of a virtual reality program attending the perspective of children. This simulation is designed to promote empathy and understanding towards children with motor disabilities through adapted sport scenes. This study proposed a validation approach with six phases to assess technical and aesthetic aspects. Method: Sample: a) In the Ccontent validity study, 20 children (11-18 years old) were recruited as lay and content experts, who assessed the properties of grade of realism and physical fidelity of wheelchair basketball scenarios. b) In the fFace validity study, 395 children were recruited as lay experts and divided into two groups (7-9 years old and 10-12 years old), or into ten subgroups according to Age x Gender interaction. The face validity sample assessed the psychological fidelity and the presence of wheelchair basketball scenarios.Instruments: Virtual Reality Content Validity Questionnaire, GAMEX questionnaire and Simulator Sickness Questionnaire (SSQ). Results: The content validity study showed preference for technical aspects (music, colors and degree of realism). Therefore, modifications in the design were made. In the content validity study, the high agreement level was influenced by previous sport experiences. In the face validity study, the cognitive development of the childchildren determined the differences in the degree of agreement levels in some virtual properties (absorption and cybersickness). In this sixth step, the Aages 7-8 years versus 10-11 years showed significant differences in validity. The study also criticized the face validity cutoffs often used in adult-focused research, emphasizing the need to adapt them for children´s commonly used in the literature, mainly derived from adult sample studies, need to be modified and adapt to the child's developmental stages. Conclusion: This study proposes a sixth step not traditionally included new methodology for establishing in content and face validity processes, specially focusing focused on the child user. The suitability of content and scenes should follow the same principles of standardization as other methodologies, such as psychometric tests, considering age and gender.